The Comparison of The Islamic and Conventional Bank Performance before and During Covid-19 Pandemic in Indonesia - Sebastiana Viphindrartin; Regina Niken Wilantari; Suryaning Bawono (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2022)
This study aims to determine and compare the financial stability of banks during the crisis which is still being debated by taking the period before and after the covid 19 pandemics. This study uses a sample of all transactions of conventional banks and Islamic banks throughout Indonesia that are recorded by the Indonesian financial services authority. With a population of all conventional financial institutions and Islamic financial institutions, both registered and unregistered by Indonesian financial services authorities throughout Indonesia. The type of data in this study is secondary data sourced from the Indonesian financial services authority. To find out and compare the performance of conventional banks with Islamic banks and the resilience of conventional banks and Islamic banks to shocks, an analysis of the financial behavior of data in commercial banks was carried out using Threshold Autoregressive. We find that Islamic banks tend to be more stable in facing financial challenges due to the COVID-19 pandemic compared to conventional banks. The performance of conventional banks was very good in the period before the COVID-19 pandemic. However, when the coronavirus pandemic began to be reported, there was a huge decline in performance. Conventional bank recovery efforts have not been able to return to the original track. Conventional bank performance is slowing down and it tends to be difficult to return to its original performance value (before the COVID-19 outbreak). However, from the graph of performance forecasting between Islamic Commercial Banks and Conventional Banks, it can be seen that there is a difference in performance stability between Islamic Commercial Banks and Conventional Banks facing the COVID-19 pandemic.